Alternatively Certified Special Education Teachers’ Implementation of PBIS - Mandy Lusk; Donna Sayman; Calli Lewis Chiu (The Advocate, 2022)
Teachers are the primary conduit through which positive behavioral interventions and supports (PBIS) are implemented. The purpose of this qualitative study is to investigate alternatively certified special education teachers’ implementation of PBIS. All participants were in their first or second year as teachers in classrooms for pre-kindergarten through twelfth grade students with disabilities. This study examines how alternatively certified special education teachers perceive and implement PBIS within their classrooms.
Keywords: PBIS; special education; alternative certification; classroom management